33‐1: All‐Inkjet‐printed AMOLED Display with Improved Efficiency and Lifetime. Issue 1 (28th June 2022) - Kim, Sehun; Kang, Taeheon; Kim, Heunggyu; Mun, Hyeran; Koo, Youngmo; Ha, Jaekook; Lee, Changhee
Abstract : Inkjet‐printing of organic light‐emitting diodes(OLEDs) is a revolutionary technology aimed at large‐size panel production, high OLED material consumption efficiency and lower manufacturing costs. Here we demonstrate all‐inkjet‐printed 12.4‐inch AMOLED display by developing a novel ink composition for ETL which enables uniform ETL formation with full orthogonality to small‐molecule EML.